Correlation between PD-L1 expression and clinical pathology, immunobiological markers, and prognosis in gastroenteropancreatic neuroendocrine neoplasms: a systematic review and meta-analysis - Zheng, Qiming; Jin, Shangbo; Xie, Xinyue; Guo, Qingjun; Chen, Chiyi; Jiang, Wentao (Frontiers in Immunology, 2026)
BackgroundAdvanced gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) have limited therapeutic options. The role of programmed death-ligand 1 (PD-L1) in their clinicopathology, immune markers, and prognosis remains controversial. This meta-analysis aimed to systematically clarify these relationships.MethodsWe searched Medline/PubMed, Web of Science, Embase, and Cochrane Library from inception to November 2025 for studies on PD-L1 expression in GEP-NENs. Two researchers independently extracted data and assessed quality via Newcastle-Ottawa Scale (NOS). Pooled analyses were conducted using Stata 17.0, with odds ratio (OR)/hazard ratio (HR) and 95% confidence interval (CI) as effect indicators, and fixed/random-effects models chosen by heterogeneity.ResultsA total of 22 studies involving 1,872 patients (17 high-quality and 5 moderate-quality) were included. High PD-L1 expression was significantly associated with higher tumor grade (OR = 3.78, 95% CI:2.04-7.01; p<0.001), poorer differentiation (OR = 2.80, 95% CI:1.18-6.65; p=0.020), increased PD-1 expression (OR = 4.15, 95% CI:2.16-7.99; p<0.001), and shorter overall survival (HR = 1.66, 95% CI:1.32-2.10; p<0.001). No significant associations were found with sex, age, histological type, tumor stage, invasion, metastasis, CD8+ T cell/FOXP3+ T cell infiltration, or mismatch repair (MMR) status. No publication bias existed.ConclusionHigh PD-L1 expression in GEP-NENs correlates with aggressive clinicopathological features, PD-1 upregulation, and unfavorable prognosis. PD-L1 may serve as a prognostic biomarker and therapeutic target for immune checkpoint inhibitors, particularly in high-grade/poorly differentiated tumors. Large-scale prospective studies are needed for validation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD420251048602.